ANALISIS PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT YASULOR INDONESIA - HERMAWATI, RAHMI (Faculty of training and education, Pamulang university, 2017)
ABSTRACTThis research is meant to find out to analyze the influence competency, discipline, and motivation to the performance of employees. The purpose of this research is to identify phenomenon and to obtain empirical evidence as well as conclusion concerning the effect of the three above mentioned variables to the performance of employees at the Production Unit of PT. Yasulor Indonesia.This research applies quantitative design, explanatory research, with hypothetical testing of survey technique, questionnaire using the scale of likert 4. The population is 240 employees from production department by employing 150 persons as samples. The technique of data analysis: (1) validity and reliability test; (2) classic assumption test; (3) determination coefficient (R2); (4) simple and multiple regression model; (5) hypothetical testing by partial test (t-test) and simultaneous test (F-test). The result of hypothetical and analytical test is as follows:1. Variable of competency (X1) has positive and significant effect on the performance of employees (Y), based on regression coefficient of 47.6% and value of t count of 0.000 (<0.05). It means that the work competency (X1) has positive and significant effect on the performance (Y)2. Variable of motivation (X2) has positive and significant effect on the performance of employees (Y), based on regression coefficient of 55.7% and value of t count of 0,000 (<0.05). It means that work motivation (X2) has positive and significant effect on the performance (Y)3. Variable of competency (X1) and motivation (X2), and simultaneously have positive and significant effect on the performance of employees (Y), based on regression coefficient of 56.1 % and value of F count of (93.981) (<2.672). It means that the competency (X1) and motivation (X2), simultaneously have positive and significant effect on the performance (Y)Based on the result of research, it is recommended that PT. Yasulor Indonesia should reanalyze the too high target of the company, provide its employee with n activity that is entertaining, spiritual, and refreshing in nature, conduct a training of synergic building team, and provide a forum of open discussion and provide a suggestion box in order to find out complaints and obstacles faced by employees during their employment. Keywords: Competency, Discipline, Motivation, and Performance